Peran Masjid dalam Pengembangan Pendidikan Agama Berwawasan Multikultural pada Masyarakat - Muchammad Eka Mahmud; Zamroni Zamroni (FENOMENA, 2014)
Islamic education, both in the context of education in the mosques and educational institutions, is always considered as a social reformation system which is an effort to strengthen the civil awarness of multiculturilism. Islamic education is being pictured as a kind of dogmatic, doctrinic, and monolitical education which has not multicultural senses. A religion, in one side, shapes a particular type of culture, or even a special culture, so that sociologically frames an exclusivenes. This is a qualitative research. The informants of this research are the employee in the mosques and the teachers. The informants were chosen using snowball sampling. The collection data techniques were observation, interview, and documentation. The data were analized by using Miles and Hubberman’s data analysis technique. The result of study shows that: the mosques, Darussalam Great Mosque and Ilamic Center Mosque, have a role to promote understanding of Islam as kaffah and rahmatan lil alamin. The roles of mosques were implemented by developing mindset and the way of thinking of the employee of the mosques, by developing the comitment of the employee and the participants of the mosques, by instructing the teachers to promote multiculturalism-based teaching.